Climate Adaptation Strategies and Revenue Implications in Smallholder Paddy Farming: Evidence From Klaten Regency - Putriesti Mandasari; Desy Mayasari; Nabittun Nahar (Jurnal Manajemen dan Agribisnis, 2026)
Background: Climate variability increasingly affects paddy production, exposing smallholder farmers to revenue instability. This challenge is also evident in Klaten Regency, Central Java, Indonesia. Although climate adaptation strategies are widely adopted, evidence on their revenue implications remains limited.Purpose: This study examines the adoption rates of climate adaptation strategies (shifting planting dates, constructing ridges, and income diversification), compares log farm revenue between adopters and non-adopters, and evaluates whether differences persist after controlling for farmer, farm, and district characteristics.Design/methodology/approach: Using primary survey data from 271 paddy farmers, adoption patterns are described using summary statistics and the mean comparison test (Welch’s t-test). Revenue associations with adaptation strategies are estimated using ordinary least squares (OLS) with three specifications. First, a baseline model that only considers adaptation indicators. Second, an OLS model with control variables (farmer and farm characteristics). Third, an OLS model with control variables and fixed effects (land tenure categories and district) to explain institutional arrangements and spatial heterogeneity.   Findings/Results: Farmers who shift planting dates tend to have higher revenue. Mean comparisons indicate higher log revenue among farmers who shift planting dates and lower log revenue among ridge users. These t-test results align with the OLS results. However, once controls are included in the OLS model, the estimated coefficients become smaller and statistically weaker, suggesting that revenue differences partly reflect farmer sorting and contextual conditions rather than direct causal effects.Conclusion: Revenue implications are heterogeneous and context-dependent. Originality/value (State of the art): This study contributes to the limited empirical evidence on climate adaptation in smallholder paddy farming by jointly analyzing adaptation strategies and farm revenue outcomes. By applying a multivariate regression framework, this study provides insights into how adaptation strategies relate to revenue under varying farmer and contextual conditions. The findings offer implications for policymakers in designing context-specific climate adaptation support. Keywords: climate adaptation, farm revenue, paddy farming, smallholder, Indonesia